Education For Waste Management Of Covid-19 Medical Mask In Pamotan Village, Porong District, Sidoarjo Regency - Aldira Mara Ditta Caesar Purwanto; Maria Novita Apriyani (Faculty of Law, 2022)
Abstract During the Covid-19 Pandemic, masks are a must-have item for almost everyone. The use of masks, which has become a new habit in society, certainly adds to the generation of waste, which if not managed properly can damage the environment. The activity is aimed at increasing the knowledge of the people of Pamotan Village, Porong District about the management of mask waste. The form of activity is in the form of lectures, discussions and questions and answers. 20 people and village officials participated in the activity. Community participation in the form of participation in socialization activities and questions asked in the question and answer session. The material presented was about the management of mask waste and about the role of the community in the management of Covid-19 medical mask waste. This activity received a good response from the Pamotan Village community and is expected to be sustainable as a form of education for the community. Keywords: Covid-19; Masks; Medical Waste; Environmental Law.